Four lenses on people management in the public sector: an evidence review and synthesis - Ali, AJ; Fuenzalida, J; Gómez, M; Williams, MJ (Oxford University Press, 2021)
We review the literature on people management and performance in organizations across a range of disciplines, identifying aspects of management where there is clear evidence about what works as well as aspects where the evidence is mixed or does not yet exist. We organize our discussion by four lenses, or levels of analysis, through which people management can be viewed: (i) individual extrinsic, intrinsic, and psychological factors; (ii) organizational people management, operational management, and culture; (iii) team mechanisms, composition and structural features; and (iv) relationships, including networks, leadership, and individuals’ relationships to their job and tasks. Each of these four lenses corresponds not only to a body of literature but also to a set of management tools and approaches to improving public employees’ performance; articulating the connections across these perspectives is an essential frontier for research. We find that existing people management evidence and practice have overemphasized formal management tools and financial motivations at the expense of understanding how to leverage a broader range of motivations, build organizational culture, and use informal and relational management practices. We suggest that foregrounding the role of relationships in linking people and performance—relational public management—may prove a fertile and interdisciplinary frontier for research and practices.